Fostering students' critical thinking by project-based learning - Pryla Rochmahwati (Journal on English as a Foreign Language, 2015)
This research focused on fostering students’ critical thinking through Project-Based Learning. The design of the research was descriptive qualitative method. The subjects were the lecturer of TEFL 1 course and 25 students in C class of the fourth semester of STAIN Ponorogo who took TEFL 1 course. The instruments used are in the form of observation sheet and interview guideline. The data analysis applied in this research used data reduction, data display, and conclusion drawing. The findings showed that the implementation Project-Based Learning that fosters the students’ critical thinking in TEFL class are through the following steps: (1) Discussing the materials about English Language Teaching Method, (2) working with the group to construct scenario of teaching practice, (3) practicing the scenario, (4) recording the teaching practice into video, and (5) evaluating the video product. Moreover, the result of interview indicates that the students showed significantly positive attitude toward the implementation of Project-Based Learning. Finally, English teachers are recommended to implement Project-Based Learning in EFL class since it facilitates the students to build their critical thinking.